ANALISIS KONTRIBUSI PAJAK KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BARITO UTARA - Muhammad Muchtar; M Faisal Abdullah; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2017)
The increase of the local government revenue has been a great cocern since more and more authority has been delegated to the local government. Therefore, the potential sources of local revenue such as the regional taxes and levies should be explored at a maximum level, but of course according to the corridor of legislation, including the motor vehicle taxes (PKB) which indeed have long become a major element of the PAD. However, the pattern of this PKB contribution to PAD of the local government, in particular the North Barito District Government has not been intensively studied. For such reason, this study was designed to determine: 1) the PKB contribution to North Barito District PAD during the period of 2012 - 2016, and 2) the potential of PKB contribution to South Sulawesi PAD from 2012 to 2016. Keywords : PAD, PKB contribution, and PKB realization